A comprehensive phylogeography of the widespread pond snail genus Radix revealed restricted colonization due to niche conservatism. Issue 24 (17th December 2021) - Saito, Takumi; Hirano, Takahiro; Ye, Bin; Prozorova, Larisa; Shovon, Mohammad Shariar; Do, Tu Van; Kimura, Kazuki; Surenkhorloo, Purevdorj; Kameda, Yuichi; Morii, Yuta; Fukuda, Hiroshi; Chiba, Satoshi
Abstract: To clarify the effect of niche conservatism on evolutionary history, we focused on freshwater snails, which have different ecological and phylogenetic properties from previously tested taxa. We conducted a phylogenetic analysis using 750 lymnaeid individuals from 357 sites of eleven Radix species. Then, we estimated the ancestral distribution using the geographic coordinates and colonization routes. In addition, a statistical test of the colonization distances in the latitudinal and longitudinal directions was performed. We also conducted ecological niche modeling for two widely distributed species using climatic data. Ancestral geographic reconstruction estimated the origin of the genus to be around the Indian subcontinental region and showed that latitudinal immigration distances were shorter than longitudinal immigration distances in the diversification process. Ecological niche models suggested that the current distribution was restricted by climate, with annual mean temperature and precipitation of the driest month as particularly strong factors. Niche conservatism to the climate can affect the diversification of freshwater snails. Abstract : To clarify the effect of niche conservatism on evolutionary history, we conducted a comprehensive phylogeography and estimation of dispersal routes. As a results, niche conservatism can affect the diversification of freshwater snails, genus Radix .